Detection and localization of flow separation on wind turbines by means of unsteady thermographic flow visualization. Issue 2 (1st May 2022) - Oehme, Felix; Sorg, Michael; Fischer, Andreas
Abstract: For the first time, a thermographic detection and localization of turbulent flow separation on an operating wind turbine is presented and verified. Flow separation on wind turbine rotor blades causes power reduction, structural loads and increased noise emissions. In contrast to established methods for stall detection, the presented infrared thermographic measurement approach is non-invasive, in-process capable and provides a high spatial resolution. With respect to the state of the art for thermographic stall detection in wind tunnel experiments, the thermal surface response to unsteady inflow conditions is evaluated for measurements on an operating wind turbine, in order to achieve unambiguous thermographic features for the detection of flow separation. The evaluation of the thermodynamic response behavior shows a clear detection of flow separation by means of temperature fluctuation maxima in the regions of flow transition as well as an increasing temperature fluctuation within the separated flow region. In addition, a geometric assignment is conducted which enables a localization of the separation point with an uncertainty of 0.6% of the chord length. The detection and localization of flow separation is verified by means of tufts visualization.